OP24 Neutralising antibody potency against SARS-CoV-2 wild-type and Omicron BA.1 and BA.4/5 variants in infliximab and vedolizumab treated patients with Inflammatory Bowel Disease after three doses of COVID-19 vaccine: a prospective multicentre cohort study. (30th January 2023) - Liu, Z; Le, K; Zhou, X; Alexander, J; Lin, S; Bewshea, C; Chanchlani, N; Nice, R; McDonald, T; Lamb, C; Sebastian, S; Kok, K; et al.
Abstract: Background: Anti-tumour necrosis factor drugs such as infliximab are associated with attenuated antibody responses after COVID-19 vaccination. It is unknown how infliximab impacts vaccine-induced serological responses against highly transmissible Omicron variants, which possess the ability to evade host immunity and are now the dominating variants causing current waves of infection. Methods: In this prospective, multicentre, observational cohort study, we investigated neutralising antibody responses against SARS-CoV-2 wild-type and Omicron BA.1 and BA.4/5 variants after three doses of COVID-19 vaccination in 1288 patients with IBD without prior COVID-19 infection, who were established on either infliximab (n=871) or vedolizumab (n=417). Cox proportional hazards models were constructed to investigate the risk of breakthrough infection in relation to neutralising antibody titres. Results: Following three doses of COVID-19 vaccine, neutralising titre NT50 (half-inhibitory neutralising titre) was significantly diminished in patients treated with infliximab as compared to patients treated with vedolizumab, against wild-type, BA.1 and BA.4/5 variants (Fig 1). Patients with Crohn's disease showed lower antibody NT50 compared to patients with ulcerative colitis against wild-type strain and BA.4/5 (Fig 2). Older age and thiopurine were independently associated with lower NT50 against wild-type strain and BA.4/5 (Fig 2). Non-white ethnicity was associated with higher NT50 compared to white ethnicity against wild-type strain, BA.1 and BA.4/5 (Fig 2). Breakthrough infection was significantly more frequent in patients treated with infliximab compared to patients treated with vedolizumab (Fig 3). Cox proportional hazards models of time to breakthrough infection after the third dose showed infliximab treatment to be associated with a higher hazard risk (HR) of 1.71 (95% CI [1.08 to 2.71], p=0.022) compared to vedolizumab (Fig 4). Higher neutralising antibody titres against BA.4/5 were associated with a lower hazard risk and a longer time to breakthrough infection (HR 0.87 [0.79 to 0.95] p=0.0028) (Fig 4). Conclusion: Following a third COVID-19 vaccine dose, patients established on infliximab treatment have significantly lower neutralising titres against SARS-CoV-2, which were especially low against Omicron variants. Increased breakthrough infection in infliximab recipients was associated with lower neutralising antibody titres against BA.4/5. These data underline the importance of continued COVID-19 vaccination programs, including second-generation bivalent vaccines, especially in patient subgroups where vaccine immunogenicity and efficacy may be reduced.